Bacterial nanocellulose and its oxidized form as functional carriers for pomegranate peel extract: A sustainable approach to bioactive delivery - Vuk Filipovic; Jasmina Nikodinovic-Runic; Katarina Savikin; Jelena Zivkovic; Jelena Mudric; Nemanja Krgovic; Marijana Ponjavic (Future Foods)
This study explores bacterial nanocellulose (BNC) and its oxidized form (o-BNC) as carriers for pomegranate peel extract (PPE) intended for functional food applications. The TEMPO-mediated oxidation was used to introduce carboxylate groups to enhance the selectivity and efficiency of adsorbed active components from PPE. Structural and compositional analyses, including FTIR and HPLC, confirmed successful incorporation of PPE components, while FESEM provided an insight into the material's morphology. In vitro release studies of ellagic acid and punicalagin, showed more sustained release of the active compounds from o-BNC which is highly influenced by pH. Antioxidant activity was evaluated by DPPH and FRAP assays, while the α-glucosidase inhibition assay was used to assess the ability to slow carbohydrate digestion, which helps regulate blood sugar levels. The o-BNC-PPE formulation exhibited significantly higher antioxidant activity than BNC-PPE, attributed to its richer phenolic content. In hypoglycemic assays, o-BNC-PPE outperformed both BNC-PPE and the standard drug acarbose, showing greater α-glucosidase inhibitory activity (IC50 1.41 μg/mL for o-BNC-PPE vs. 29.1 μg/mL for BNC-PPE and 156.6 μg/mL for acarbose). Compared to unmodified BNC, a wider range of bioactive compounds was incorporated on o-BNC due to enhanced binding capacity and porosity, which translated into material stronger antioxidant activity, attributed to presence of additional phenolics like gallic acid and ellagitannins. These findings underscore the potential of BNC-based materials as carriers of natural bioactive compounds in functional foods, offering a sustainable approach to delivery of antioxidants and other health-promoting bioactive compounds through diet, while also supporting plant waste valorization.